MODERN METHODOLOGIES FOR EFFECTIVE BIOLOGY TEACHING - Gulustan Asadova Vugar (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Modern methodologies for effective biology teaching have revolutionized the way educators approach scientific instruction, shifting from traditional lecture-based formats toward dynamic, student-centered learning environments. This paper examines a range of innovative pedagogical strategies designed to enhance student engagement, comprehension, and retention of complex biological concepts. Key methodologies explored include inquiry-based learning, project-based instruction, flipped classroom models, and the integration of digital technologies such as virtual laboratories, interactive simulations, and multimedia platforms. Additionally, collaborative learning approaches and formative assessment techniques are analyzed for their role in fostering critical thinking and scientific reasoning among students at various academic levels. The study highlights the importance of aligning teaching methods with diverse learning styles and the growing need to incorporate real-world applications to make biology relevant and accessible. Findings suggest that a blended approach, combining traditional instruction with modern, technology-enhanced strategies, yields the most significant improvements in academic performance and scientific literacy. Implications for curriculum design, teacher professional development, and future research directions are also discussed.